Enhancing Quranic Literacy: The Role Teacher and Parental Involvement in Quran Learning - Hanafi, Muhammad; Pohan, Selamat (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
PAI teachers play an essential role in Islamic education, especially in developing students' Qur'an reading skills, including tajweed, Maharaj, and fluency, while fostering spiritual growth. This study examines the teaching strategies, challenges, and outcomes of the Qur'an literacy program at SMP Negeri 2 Pegajahan using a qualitative case study design. Data were collected through direct observation, semi-structured interviews with teachers, students, parents and school leaders, and document analysis such as lesson plans and student performance records. Data analysis was conducted based on the Miles and Huberman framework through the stages of reduction, presentation, and conclusion drawing, with the support of triangulation techniques to ensure data validity. The results showed that PAI teachers act as facilitators as well as spiritual mentors, using effective teaching methods such as iqra' and talaqqi to build Qur'anic literacy. The daily routine of reading the Qur'an before the lesson begins increases motivation, builds confidence, and encourages students' spiritual discipline. Collaboration with parents and support from school leaders, including the provision of additional study time and interactive media, significantly strengthened the effectiveness of the program. This research contributes to the discourse of holistic Islamic education by demonstrating the integration of intellectual, emotional and spiritual elements in pedagogy. The study also offers practical recommendations for teachers and policymakers in designing innovative Qur'ānic literacy programs, which ultimately benefit educational institutions and the wider community